Sales and Purchases Of Sharia Mutual Funds Impact During Covid-19 Pandemic - Atika Zahra Maulida Atika; Agus Purnomo (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2022)
The outbreak of the COVID-19 virus has had an impact on the world economy and the country. The Covid-19 outbreak that has hit the whole world has resulted in countries implementing policies to reduce the spread of the COVID-19 virus by implementing a lockdown, restricting business activities, and banning long-distance travel. In 2020 sharia mutual funds sold 289 portfolios and in 2021 sharia mutual funds sold 295 lots. The development of Net Asset Value performance in sharia mutual fund products from 2015 to 2021 was 74.37%. The existence of the covid 19 virus does not affect the buying and selling transactions of Islamic mutual funds. The research method uses descriptive quantitative methods. In collecting data, the researchers distributed a questionnaire of 100 respondents to investors, investment managers, and the public in South Kalimantan. in 2018 to 2019 the number of investors was 53,735.58 while in 2019 to 2020 the number of investors reached 74,367.44 and from 2020 to 2021 the number of investors was 72,668.70 even though the pandemic was ongoing. Keywords: Sales, Purchases, Sharia Mutual Transactions and covid 19.